The Degree of Curriculum Development in the First Three Primary Grades and its Role in Students’ Qualitative Performance from the Point of View of Teachers Working in Public Schools in the Governorate of Aqaba - Abu Eisheh, Amani (Dirasat: Educational Sciences, 2020)
The study aimed to determine the degree of curriculum development in the first three basic grades and its role in students’ qualitative performance from the point of view of teachers in public schools in the governorate of Aqaba. The study population consisted of all the teachers of the three primary grades in the public schools in Aqaba totalling (239) teachers. 106 teachers of them were chosen randomly during the academic year of 2019-2020. Therefore, the questionnaire was used as an instrument to collect data for the study. The results of the study revealed that the curriculum development degree for the first three elementary grades from the point of view of teachers was high. Furthermore, the level of qualitative performance of students in the first three grades from the point of view of teachers in public schools in Aqaba Governorate was moderate. The results also showed there was a correlation between the degree of curriculum development in the first three primary grades and its role in students’ qualitative performance.